Involvement in Child Rearing and Firm Control Parenting by Male Cohabiting Partners in Black Low-Income Stepfamilies: Forecasting Adolescent Problem Behaviors. (September 2015) - Forehand, Rex; Parent, Justin; Golub, Andrew; Reid, Megan; Lafko, Nicole
Cohabitation is a family structure that is rapidly increasing in the United States. The current longitudinal study examined the interplay of involvement in a youth's daily activities and firm control parenting by male cohabiting partners (MCPs) on change in adolescents' internalizing and externalizing problems. In a sample of 111 inner-city African American families, adolescents reported on involvement and parenting by MCPs at Wave 1 and biological mothers reported on adolescent problem behaviors at Waves 1 and 2. A significant interaction indicated that low involvement and low firm control by MCPs at Wave 1 were associated with the highest level of internalizing problems at Wave 2. An interaction did not emerge when externalizing problems served as the outcome. The findings indicate that male partners play an important role in parenting adolescents in cohabiting families and should be considered potential participants in prevention and intervention programs.